Perencanaan tata hijau jalan berdasarkan fungsi jalan di Kota Denpasar - Sun’iyyah, I’in Lathifatus; Sukewijaya, I Made; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018, 2018)
The planning of green street system in Denpasar City based on street function. Denpasar city is the capital of Bali Province which is currently experiencing growth and development, one of them is street accretion in length and improvement which is continue to grow every year. Based on street function, Denpasar has three street type e.g. arterial street, collectoral street and local street. Each street has different functions and criteria that require different green street system as well as having to adjust the function and criteria of the street. The purpose of this study was to plan a green street system in accordance with the existing street function in Denpasar. Method used in this research were observation and literature study. The concept applied was the green street system aligned with functional plants. Research showed that the concept of the street was improved by implementing collaboration of between space and green concept. The findings of this research was the planning of green street system based on street function which was adjusted to the condition of its surrounding area.